PERBANDINGAN MODEL PEMBELAJARAN SAVI DAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI BANJIR - Francisca, Helga Dwiyantie; Jayadinata, Asep Kurnia; Sudin, Ali (Jurnal Pena Ilmiah, 2019)
improve students' critical thinking skills. The learning model is the Somatic, Auditory, Visual and Intellectual (SAVI) and Cooperative Type Jigsaw learning models. The Somatic, Auditory, Visual, and Intellectual (SAVI) and Cooperative Type Jigsaw learning models are the right way to improve students' critical thinking skills. In the learning process, the SAVI learning model and Cooperative Type Jigsaw use physical movements to improve the thinking or mental processes, and through facilitating a variety of learning styles that each student has. The purpose of this study was to determine the differences in the improvement of students' critical thinking skills in flood material through the SAVI learning model and Type Jigsaw Cooperative. The design of this study was quasi-experimental. The population in this study were all elementary school students in the Tanjungsari District. The sample technique used was purposive sampling, so that the samples obtained were SDN Mariuk as the experimental class and Lebakgede Elementary School as the control class. The instruments used were test instruments in the form of tests of critical thinking skills, and non-test instruments in the form of student response questionnaires, observation of student activities, and observation of teacher performance. Based on the results of the study, it was found that learning using the SAVI learning model had a positive effect on students 'critical thinking skills when compared to the Cooperative Type Jigsaw learning model which gave little influence on students' critical thinking skills. The response of students in the experimental class and the control class was different, even though the two classes gave positive responses but the responses of students in the experimental class were higher than the responses of students in the control class.